Prevalence and risk predictors of onychomycosis in patients on hemodialysis: an observation, prospective, and unicenter study in Brazil - Bersano, Jeanne Marie Queiroz Borges; Cordeiro, Matheus Gobbo; Marson, Fernando Augusto Lima (Frontiers in Medicine, 2023)
Background: Onychomycoses are fungal infections that can involve any component of the nail unit, including the matrix, bed, and plate, and are caused by dermatophyte fungi, non-dermatophyte fungi, and yeasts. This disease affects around 1% to 8% of the general population and occurs in about 19% to 51.9% of the patients on hemodialysis. The high incidence of onychomycosis in patients on hemodialysis is associated, mainly, with immunological deficit and histological changes caused by uremia. Methods: Adult patients of the São Francisco University Hospital Hemodialysis Center were included. The following characteristics were evaluated: age, sex, body mass index, comorbidity, and household location. All patients were clinically evaluated and those with suspected onychomycosis had subungual debris of the affected nail plate collected for the direct mycological examination and fungal culture. Results: The study included 151 patients, and 70/151 (46.4%) showed nail alteration, and among them, 31/70 (44.3%) had the onychomycosis diagnosis confirmed by direct mycological examination. The pathogens observed in the patients were: Trichophyton rubrum [8/31 (25.8%)], Trichophyton mentagrophytes [7/31 (22.6%)], Scytalidium spp. [6/31 (19.4%)], Candida spp. [2/31 (6.45%)], Rhodotorula spp. [1/31 (3.2%)], Candida albicans [1/31 (3.2%)], Penicillium marneffei [1/31 (3.22%)], and T. rubrum and Rhodotorula spp. [1/31 (3.2%)]. The nail involvement severity score was majority severe [23/27 (85.2%)]. In the bivariate analysis, a higher risk of onychomycosis was associated with the male sex [23/31 (74.2%) vs. 56/120 (46.7%); OR=3.286 (95%CI=1.362-7.928)] and obesity [8/31 (25.8%) vs. 12/120 (10.0%); OR=3.130 (95%CI=1.150-8.521)]. The multivariable model using the Logistic Regression (Backward model) confirmed our results and it was able to predict (81.5%) the onychomycosis positive diagnosis (P-value<0.001). The age [OR=1.036; 95%CI=1.004-1.069], male sex [OR=5.746; 95%CI=2.057-16.046], and presence of obesity [OR=4.800; 95%CI=1.435-16.055] were positive and significant in predicting the onychomycosis positive diagnosis. Conclusion: Onychomycosis in patients on hemodialysis was associated with a great variety of microorganisms mainly Trichophyton species. The nail involvement severity score was majority severe among those patients and distalsubungual onychomycosis and mixed pattern onychomycosis were the most prevalent clinical types. The main risk factors associated with onychomycosis were male sex, older age, and presence of obesity.